Matriarchy in Bronze Age Crete A Perspective from Archaeomythology and Modern Matriarchal Studies - Cichon, Joan M. (Archaeopress Publishing, 2022)
"Matriarchy in Bronze Age Crete: A Perspective from Archaeomythology and Modern Matriarchal Studies offers a very different perspective of Crete than is usually found in academic writing; making a compelling case for a matriarchal Bronze Age Crete. Bronze Age Crete evokes for many the image of an exceptionally sophisticated civilization: peaceful, artistic, and refined; a society in which women were highly visible and important, and the supreme deity was a Goddess. Yet, despite the fact that authorities acknowledge that the preeminent deity of Crete was a Female Divine, and that women played a major role in Cretan society, there is a gap in the scholarly literature, and a lively, ongoing debate regarding the centrality of women and the existence of matriarchy in Bronze Age Crete. The purpose of this work is to fill that gap, and to advance the debate over whether or not ancient Crete was a woman-centered and matriarchal society toward a more complex, detailed, and certain conclusion. To that end this publication utilises the field of modern matriarchal studies, with its carefully elucidated definition of the term matriarchy, and employs the methodology of archaeomythology - the use of historical, mythological, linguistic, and folkloric as well as archaeological sources. Given its scope, the volume will be of interest to scholars and students in the fields encompassed by archaeomythology, as well as the fields of women's studies, women's history, women's spirituality, and modern matriarchal studies."